Multi-messenger searches via IceCube's high-energy neutrinos and gravitational-wave detections of LIGO/Virgo - Veske, Doğa; Hussain, Raamis; Márka, Zsuzsa; Countryman, Stefan; Pizzuto, Alex; Asali, Yasmeen; Oliveira, Ana Silva; Vandenbroucke, Justin; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; et al. (Proceedings of Science, 2022)
We summarize initial results for high-energy neutrino counterpart searches coinciding with gravitational-wave events in LIGO/Virgo's GWTC-2 catalog using IceCube's neutrino triggers. We did not find any statistically significant high-energy neutrino counterpart and derived upper limits on the time-integrated neutrino emission on Earth as well as the isotropic equivalent energy emitted in high-energy neutrinos for each event.
CRIS-Team Scopus Importer:2024-12-16